108 Developing A Non-Biopsy Protocol for The Female Cohort 25-29 Years with Clinically Typical Fibroadenoma Conforming to Maxwell Criteria on Ultrasound – Our Peninsular Experience in Wirral. (4th May 2021) - Arif, T; Vinayagam, R
Abstract: Introduction: The aim of this study was to introduce a non –biopsy protocol in our department for benign breast lump referrals confirmed as typical U2/3 fibroadenoma on imaging. Current UK guidance is not to biopsy sonographically typical fibroadenoma in women under 25 years. We have studied our population extending the radiological Maxwell criteria reflecting benign outcomes in 25-29 years cohort. Method: Retrospectively data was collected of all women between 25-29 years of age undergoing core biopsies for ultrasound confirmed fibroadenoma between 2014 and 2019 over a period of five years. The number of cancers picked up was compared with the number of referrals and the discordance between radiological diagnosis of fibroadenoma and histopathological confirmation of malignancy was recorded. Results: A total of 1707 referrals were made across five years. n = 175 image guided core biopsies were carried out for U2, U3, U4 lesions appearing as fibroadenoma on ultrasound. Out of these (n = 175), all lesions coded U2/3 (n = 165) based on Maxwell criteria on ultrasound were negative for cancer. U4 lesions on ultrasound were confirmed as cancers mimicking fibroadenoma(n = 10). Conclusions: This retrospective audit of 1707 patients provides sound evidence for non-biopsy of typical fibroadenoma in 25–29 years cohort sonographic features meet strict criteria.